2019
DOI: 10.1101/575480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct Sequencing of RNA with MinION Nanopore: Detecting Mutations based on Associations

Abstract: These authors contributed equally One of the key challenges in the field of RNA virus genetics is the inference of full haplotypes from next generation sequencing data. The MinION Oxford Nanopore sequencer allows sequencing very long reads, with the potential of sequencing the complete genomes of RNA viruses in individual reads. However, MinION suffers from high error rates, rendering the detection of true viral mutations very difficult. Here we propose a new statistical approach to differentiate between true … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…To test whether the various presumably defective mutants are independent or not, we performed direct long-read RNA sequencing using MinION by Oxford Nanopore. We sequenced more than 15,000 full genomes from p15 of lines A and B and used an approach that we have recently developed to overcome the high error rate of MinION (Methods) (44). Our results revealed that 1764 and the second most prominent mutation in the experiment, A1664G, are independent and do not reside on the same genomes.…”
Section: The Mechanism Of Defection Of the Deletion Mutantmentioning
confidence: 99%
See 2 more Smart Citations
“…To test whether the various presumably defective mutants are independent or not, we performed direct long-read RNA sequencing using MinION by Oxford Nanopore. We sequenced more than 15,000 full genomes from p15 of lines A and B and used an approach that we have recently developed to overcome the high error rate of MinION (Methods) (44). Our results revealed that 1764 and the second most prominent mutation in the experiment, A1664G, are independent and do not reside on the same genomes.…”
Section: The Mechanism Of Defection Of the Deletion Mutantmentioning
confidence: 99%
“…Illumina MiSeq library preparation and read alignment were performed as described in (44). Briefly, the MS2 RNA was reverse-transcribed using SuperScript III Reverse Transcriptase (Thermo Fisher Scientific), using 3R primer (TGGGTGGTAACTAGCCAAGCAG).…”
Section: Illumina Miseq Library Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out in [ 6 ], it is difficult to give a universal definition of microbial strain. Depending on the context, strain can refer to a virus variant with unique and stable phenotypic characteristics under natural conditions [ 7 ], or a specific viral genome [ 3 , 6 , 8 – 10 ]. In this context, strain refers to a specific viral genome.…”
Section: Introductionmentioning
confidence: 99%
“…The Nanopore sequencing platforms sequence DNA or RNA in one run. Nanopore DNA sequencing technology was developed first, with lower error rates (the per-nucleotide error rate is~5%-15% (Luo et al, 2019)) and higher throughput than direct Nanopore RNA sequencing (the pernucleotide error rate is approximately 17.02% (Harel et al, 2019)). During the Ebola outbreak in Guinea, Quick et al designed an entire sequencing system based on the MinION platform of the ONT Company, which could be accommodated in a single ordinary test bed, for real-time genome monitoring of the epidemic (Quick et al, 2016).…”
mentioning
confidence: 99%